Remittances and development in Latin-American. Myths and facts - Canales, Alejandro I. (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
The amount that remittances have achieved is not only a public opinion issue, but an emergent topic for politics and social sciences. However, there is no consensus about the social effects and economic impacts of remittances. On one hand, the international organizations for development, as well as several governments, have paid special attention to remittances as a tool that would contribute to the reduction of poverty and to the development of the regions of origin of international migration. On the other hand, many academics and civil organizations are skeptical about it as they think that remittances are just transferences between particulars, so they can´t substitute the state and the market’s role in the promotion of economic development and population’s welfare. This article contributes to this controversy from a positive point of view with analytical elements and empirical information that allow us to sustain a critical position about the role of remittances in the development of Latin America
Keywords: Remittances; Development; International Migration